Peran Media Sosial Youtube sebagai Media Edukasi dalam Pendidikan Generasi Z - Tri Ayu Mareta; Desty Endrawati Subroto; Lailaturrohmah Aulia; Siti Nuryanah; Ratu Najwa Fadilah (Politeknik Kampar, 2025)
Generation Z, born between 1997 and 2012, has grown up in the digital era and is highly familiar with technology. Social media, particularly YouTube, has become one of the primary sources of information and learning for this generation. This study aims to explore the role of YouTube as an educational medium in the learning process of Generation Z.The research findings indicate that YouTube has become an effective learning resource for Generation Z. The platform provides access to a variety of educational content, ranging from tutorial videos, online lectures, to documentaries. Additionally, YouTube enables interaction among users, facilitating discussions and collaborative learning. However, the study also identifies several challenges in using YouTube as an educational tool. One challenge is the inconsistent quality of content, which requires careful filtering and evaluation. Furthermore, using YouTube for educational purposes necessitates critical and analytical skills to distinguish between accurate and inaccurate information. Overall, the study demonstrates that YouTube can be an effective educational medium for Generation Z, but it requires strict oversight and evaluation to ensure the quality of content and effective learning outcomes.